Aplikasi Biogrouting Untuk Meningkatkan Kestabilan Deposit Tebing Sungai Dari Material Piroklastik - Murtadli, Imtazul; Primantyo, Andre; Yuliani, Emma (Fakultas Teknik, Universitas Brawijaya, 2021)
Mount Kelud is one of the active volcanoes in Indonesia, where its eruption activity produces pyroclastic material. The mass distribution of pyroclastic material causes the probability of landslide is increasing. This study aims to investigate the physical characteristic including the classification of pyroclastic material from Mount Kelud and also to study the effectiveness of biogrouting application as a way to increase the shear strength of pyroclastic material. The initial soil sample has a well-graded condition with Gs = 2,651. After biogrouting treatment performed, the soil sample shows an increasing value of the angle of internal friction in original and fine sample, where as the coarse sample shows the opposite effect. The highest value of the angle of internal friction is owned by original gradation with w=10% and increasing percentage up to 126,18% based on the initial sample. On the other hand, the three gradations have an increasing value for cohesion parameter, with the highest increasing value owned by coarse sample by w = 10% from 0,0183 kg/cm2 to 0,7687 kg/cm2 based on natural sample as a control.